Molecular Resonance Generator (MRG) Assisted Tonsillectomy - An Innovative Technique - Hamsa Shetty; Gangadhara KS; Sridhara S (Bengal Journal of Otolaryngology and Head Neck Surgery, 2023)
Introduction-Dissection and Snare method of tonsillectomy was first introduced nearly a century ago. Since then several methods of performing tonsillectomy have evolved like electrocautery, harmonic scalpel ,Laser, coblation and Magnetic Resonance Generator(MRG). All these methods have been used with the aim of overcoming the shortcomings with the previous methods like intra and post operative bleeding ,reducing the duration of surgery and post operative pain.MRG works on the principle of quantum resonance and it has helped in minimizing the intraoperative and post operative bleeding as well as post operative pain.In this study MRG was used for tonsillectomy with favourable outcome.